Application of mesenchymal stem cell-derived exosomes from different sources in intervertebral disc degeneration - Xia, Yuanliang; Yang, Ruohan; Hou, Yulin; Wang, Hengyi; Li, Yuehong; Zhu, Jianshu; Fu, Changfeng (Frontiers in Bioengineering and Biotechnology, 2022)
Intervertebral disc degeneration (IVDD) is one of the main causes of lower back pain. IVDD directly causes psychological and economic burdens to patients. Physical therapy only delays pain in patients, but cannot eliminate the cause of IVDD. Surgery is required when the patient cannot tolerate pain or has severe neurological symptoms. Although surgical resection of the IVD or decompression of the laminae eliminates the diseased segment, it will damage the adjacent normal IVD. There is also a risk of re-protrusion after IVD removal. Cell therapy has played a crucial role in the development of regenerative medicine. Cell transplantation promotes regeneration of degenerative tissue. However, due to the lack of vascular structure in the IVD, sufficient nutrients cannot be provided for transplanted mesenchymal stem cells (MSCs). In addition, dead cells release harmful substances that aggravate IVDD. Extracellular vesicles (EVs) have been extensively studied as an emerging therapeutic approach. EVs generated by paracrine MSCs retain the potential of MSCs and serve as carriers to deliver their contents to target cells to regulate target cell activity. Due to the double-layered membrane structure of EVs, they have low immunogenicity and no immune rejection. Therefore, EVs are considered an emerging therapeutic modality in IVDD. However, EVs face the disadvantages of mass production and low loading rates. In this review, the structure of IVD and the advantages of EVs are first introduced. Next, the application of MSC-EVs in IVDD is discussed. Finally, the shortcomings of EVs are introduced, and future applications are described.